Approximation in enumeration techniques for large scale zero-one programming for corporate average fuel economy planning - Kostreva, M.M. (IEEE International Conference on Systems, Man and Cybernetics, 1990, 1990)
Mathematical programming was used to achieve corporate average fuel economy standards at minimum cost. Computational difficulties were experienced on the large-scale zero-one linear integer programming problems that arose. To alleviate these difficulties, a method based on adaptive estimates of the optimal objective function value was implemented in a computer code using implicit enumeration. With this approach the computational problems encountered in determining minimum-cost allocation of mass and/or fuel-efficient components among car lines are reduced substantially. Results are presented showing that problems with 100 to 350 variables are handled easily and solved within a minute. These enhanced capabilities permit extensive sensitivity analyses, and thus provide numerous practical alternatives to the decision-maker.< >